Determinants of aortic stiffness: 16-year follow-up of the Whitehall II study. - Nanna B Johansen; Dorte Vistisen; Eric J Brunner; Adam G Tabák; Martin J Shipley; Ian B Wilkinson; Carmel M McEniery; Michael Roden; Christian Herder; Mika Kivimäki; Daniel R Witte (PLoS ONE)
Background Aortic stiffness is a strong predictor of cardiovascular disease endpoints. Cross-sectional studies have shown associations of various cardiovascular risk factors with aortic pulse wave velocity, a measure of aortic stiffness, but the long-term impact of these factors on aortic stiffness is unknown. Methods In 3,769 men and women from the Whitehall II cohort, a wide range of traditional and novel cardiovascular risk factors were determined at baseline (1991-1993) and aortic pulse wave velocity was measured at follow-up (2007-2009). The prospective associations between each baseline risk factor and aortic pulse wave velocity at follow-up were assessed through sex stratified linear regression analysis adjusted for relevant confounders. Missing data on baseline determinants were imputed using the Multivariate Imputation by Chained Equations. Results Among men, the strongest predictors were waist circumference, waist-hip ratio, heart rate and interleukin 1 receptor antagonist, and among women, adiponectin, triglycerides, pulse pressure and waist-hip ratio. The impact of 10 centimeter increase in waist circumference on aortic pulse wave velocity was twice as large for men compared with women (men: 0.40 m/s (95%-CI: 0.24;0.56); women: 0.17 m/s (95%-CI: -0.01;0.35)), whereas the opposite was true for the impact of a two-fold increase in adiponectin (men: -0.30 m/s (95%-CI: -0.51;-0.10); women: 0.61 m/s (95%-CI: -0.86;-0.35)). Conclusion In this large prospective study, central obesity was a strong predictor of aortic stiffness. Additionally, heart rate in men and adiponectin in women predicted aortic pulse wave velocity suggesting that strategies to prevent aortic stiffening should be focused differently by sex.